Effect of Dexamethasone-Loaded PLGA Nanoparticles on Oral Mucositis Induced by 5-Fluorouracil - Ribeiro, Susana Barbosa (2021)
Oral mucositis (OM) is characterized by the presence of severe ulcers in the oral region that affects patients treated with chemotherapy. It occurs in almost all patients who receive radiotherapy of the head and neck, as well as patients who undergo hematopoietic cell transplantation. The pathophysiology of OM is complex, and there is no effective therapy. The aim of this study was to evaluate the effect of dexamethasone-loaded poly(D,L-Lactic-co-glycolic) nanoparticles (PLGA-DEX NPs) on an OM model induced in hamsters. The NPs were synthesized using the emulsification-solvent evaporation method and were characterized by the size, zeta potential, encapsulation efficiency, atomic force microscopy, physicochemical stability, and the in vitro release. The OM was induced by the administration of 5-FU on the first and second days and mechanical trauma on the 4th day of the experiment. PLGA-DEX NPs were administered to treat OM. The animals were euthanized on the 10th day. Macroscopic and histopathological analyses were performed, measurement of malonaldehyde (MDA) and ELISA was used to determine the levels of IL-1β and TNF-α. Immunoexpressions of NF-κB, COX-2, and TGF-β were determined by immunohistochemistry, and qRT-PCR was used to quantify the gene expression of the GILZ, MKP1, and NF-κB p65. The PLGA-DEX NPs (0.1 mg/kg) significantly reduced macroscopic and histopathological scores, decreased MDA, TNF-α and IL-1β levels, immunostaining for NF-κB, COX-2, TGF-β, and suppressed NF-κB p65 mRNA expression, but increased GILZ and MKP1 expression